Development of a sustainability transmedia campaign for the corporate strategy of the Aveiro Port - Cuellar Quiroz, Tatiana (2024)
As corporations globally seek to integrate sustainable practices and environmental awareness into their strategies, effective communication becomes essential. As a key player in the maritime industry, the Aveiro Port recognizes the need to communicate its commitment with the environmental responsibility in a compelling and impactful manner. Considering this necessity, transmedia storytelling tends to be a dynamic and immersive approach to communicate this message, given the spreading content over multiple platforms. This development research subdivided into three phases has, therefore, the purpose of identifying the strategies that can be used to effectively communicate corporate environmental sustainability. The first phase explores the theoretical foundations of transmedia storytelling, environment corporate sustainability, and audiovisual communication, through a comprehensive literature review, and needs assessment through semi-structured interviews with three stakeholders. The second phase involved the design and development of a sustainability transmedia campaign as a corporate strategy for the Aveiro Port. Then phase 3 proposes the metrics to evaluate the campaign, presenting recommendations for future evaluations of the campaign’s impact. As a result, this research establishes the basis for creating transmedia sustainability campaigns, which can be further explored and tested in future research. This dissertation contributes with valuable insights into the design of transmedia storytelling strategies to effectively communicate corporate environmental responsibility, providing a model that can be adapted and refined in future studies.